Developing EFL Students’ Writing Skill Through Self-Assessment Integrated With E-Portfolio - Moh. Taufik; Bambang Yudi Cahyono (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
ABSTRACTWriting is one of the language skills that should be mastered by students of English as a foreign language (EFL). In order to write well, EFL students should understand the content of their writing. They should also be able to discover some writing errors they may have. Therefore, it is necessary for the students to practice writing frequently and to be willing to review their writing products. This study aimed to develop EFL students’ writing skill through self-assessment integrated with e-portfolio. It used action research design and it was conducted in a classroom consisting of 25 ten graders of Islamic Senior High School (Madrasah Aliyah Negeri) at Sumenep, East Java. The findings showed that the students’ writing skill could be improved after the implementation of self-assessment integrated with e-portfolio. It is suggested that EFL teachers consider using self-assessment integrated with students’ e-portfolio to help improve EFL students’ writing skill.ABSTRAKMenulis merupakan kemampuan berbahasa yang harus dimiliki oleh pelajar bahasa Inggris sebagai bahasa asing (EFL). Dalam mengembangkan kemampuan menulis, pelajar dituntut untuk mengerti isi tulisan mereka dan mampu menemukan kesalahan-kesalahan yang mungkin terdapat dalam tulisan mereka. Maka dari itu, pelajar dipandang perlu untuk sesering mungkin melatih kemampuan menulis, mengulas kembali dan merevisi karya mereka. Penelitian ini bertujuan untuk mengembangkan kemampuan menulis siswa menggunakan self-assessment melalui elektronik portofolio. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) dengan subjek 25 siswa kelas X MAN Sumenep, Jawa Timur. Penemuan penelitian ini menunjukkan bahwa kemampuan menulis siswa membaik setelah penerapan self-assessment melalui elektorinik portofolio. Dengan demikian, guru bahasa Inggris disarankan untuk mempertimbangkan penerapan sefl-assessment melalui elektronik portfolio siswa untuk mengembangkan kemampuan menulis siswa. How to Cite: How to Cite: Taufik,M., Cahyono, B. Y. (2019). Developing EFL Students’ Writing Skill Through Self-Assessment Integrated With E-Portfolio. IJEE (Indonesian Journal of English Education), 6(2), 171-186. doi:10.15408/ijee.v6i2.12019